How New Graduate Nurses Address Sexual Harassment from Patients in the Workplace: An Interpretive-Descriptive Study - Marshall, Helen Jane (Auckland University of Technology, 2026)
International studies show that sexual harassment of nurses is a major concern and is more likely to occur with younger nurses. The first two years of nursing practice are a crucial phase for new graduate nurses to build confidence. They can experience transition shock as they move from the student nurse role to registered nursing responsibilities. This transition shock is unavoidable, but its effects can be mitigated in a supportive environment. A new graduate nurse faced with sexual harassment can experience psychological and physical effects. Therefore, the support they receive can be crucial in their decision to leave the profession or remain in nursing. Due to the worldwide nursing and staffing retention issues, appropriate support is vital to retain new graduate nurses if they experience any stressors, such as sexual harassment. This qualitative study aimed to investigate how new graduate nurses addressed sexual harassment from patients during the first two years of their post-graduation practice. Another aim was to identify the types of sexual harassment new graduate nurses experienced, including whether they reported this harassment, if this sexual harassment affected their practice and whether this sexual harassment affected their decision to remain in nursing as a career. It also aimed to determine what education and support they have received or need after experiencing sexual harassment. This study focused only on the new graduate nurses' experience of sexual harassment by patients, and this specific focus allowed for coherent data analysis. This study employed an interpretive-descriptive approach, underpinned by naturalistic inquiry, to explore how new graduate nurses in their first two years of practice addressed sexual harassment from patients. Five participants were recruited through extensive advertising. Questions were carefully scaffolded, encouraging respondents to share their experiences of sexual harassment from patients in their workplace. Using thematic analysis, five themes were identified. 1) “Did that just happen? It was a shock;” 2) “It’s taboo, not spoken about;” 3) “It changed my practice;” 4) Expecting respect but making allowances; 5) A culture of “silence” – the need for organisational change. This study addressed a gap in the literature, as no prior studies had examined how new graduate nurses address sexual harassment from patients during their first two years of practice. This research identified a need for education on the definitions of sexual harassment and strategies for addressing this issue, both during nursing training and for all practising nurses. When these new graduate nurses experienced sexual harassment from patients, there was a demonstrated lack of intervention and support from colleagues and leadership. This study has shown that there needs to be changes in the organisational culture both within nursing education and workplaces. This will ensure any form of sexual harassment is recognised and seen as unacceptable. Incident reporting needs to be encouraged to decrease the organisational silence regarding sexual harassment, and follow-up support for those who experience sexual harassment must be mandatory. This research builds a platform for further research regarding sexual harassment in health organisations to help support the nursing workforce in Aotearoa New Zealand.